TINGKAT STRESS PADA SISWA DALAM MENGIKUTI FULL DAY SCHOOL - Niken Palupy Maiyun; Ida Nur Imamah (Journal Keperawatan, 2023)
Full day school system in Indonesia had actually been running before the existence of a policy from the Ministry of Education and Culture, namely in private schools, international schools and religious-based schools such as Islamic boarding schools. The full day system allows children to lose some of their playing time due to the long study time at school. Children with a full day school system have a higher stress level than children with a half day school system. This is because children study at school until 15.30. Long study time results in reduced playing time for children so that children get bored easily. Adequate play time for children will have a good impact on children, they will tend not to feel a burden on themselves .Objective to determine the description of the level of stress on students in attending full day school SMA Batik 2 Surakarta. Methods This type of research is quantitative with a descriptive approach. Sampling of 96 respondents. The research instrument used the Perceived Stress Scale (PSS) questionnaire. Data analysis using Univariate test. The results showed that the majority of student categories based on gender were female as many as 47 (52.2%) and the description of the level stress on students attending full day school was the majority of respondents with severe stress levels of 52 students or 57.8% and minority respondents were mild stress level with a total of 7 students or 7.8% . Conclusion the description of the level of stress on students in attending full day school at SMA Batik 2 Surakarta is relatively high with the results being the majority of 52 people (57.8%) in the severe stress category.